2001
DOI: 10.1007/s10434-001-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Isotope Injection: A Highly Accurate Method of Lymphatic Mapping in Breast Carcinoma

Abstract: These data demonstrate that intradermal injection of radioactive tracer is an effective method of localizing the SLN in cases involving small breast cancers. Further investigation is warranted before this technique is adopted for use in larger breast cancers. Intraoperative examination and biopsy of any suspicious nonsentinel nodes are critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Our own technique evolved over our first 1000 procedures. 10 In a logical sequence of studies, we have previously demonstrated (1) the complementarity of isotope and blue dye, 8 -11 (2) the superiority of unfiltered over 220 nm filtered 99m Tc-labeled sulfur colloid, 12 (3) the advantage of intradermal over intraparenchymal isotope injection, 13,14 and (4) an overall success in identifying the SLN, which continued to increase over our first 500 procedures. 15 We also demonstrated (5) that false negative results were most common in the early experience of each surgeon.…”
Section: Discussionmentioning
confidence: 78%
“…Our own technique evolved over our first 1000 procedures. 10 In a logical sequence of studies, we have previously demonstrated (1) the complementarity of isotope and blue dye, 8 -11 (2) the superiority of unfiltered over 220 nm filtered 99m Tc-labeled sulfur colloid, 12 (3) the advantage of intradermal over intraparenchymal isotope injection, 13,14 and (4) an overall success in identifying the SLN, which continued to increase over our first 500 procedures. 15 We also demonstrated (5) that false negative results were most common in the early experience of each surgeon.…”
Section: Discussionmentioning
confidence: 78%
“…As a consequence, one of the current fields of investigation is determining the best injection site for sentinel node identification [6,7]. Some data seem to suggest that a retro-areolar injection could be adequate for the majority of tumor localization in the breast [8,9].…”
Section: Discussionmentioning
confidence: 98%
“…Sentinel lymph node biopsy may result in a false negative in 1-15% of patients [7][8][9]. Most of these false-negatives are due to massive lymph node metastasis in the first drainage node, which divert lymphatic drainage away from the node [25]. When an attempt to apply sentinel lymph node biopsy for larger tumors is made, PET/CT might serve to identify patients at risk of a false-negative sentinel lymph node biopsy [19].…”
Section: Discussionmentioning
confidence: 99%